Hadith #2166 - Sunan Abi Dawud - Abdullah ibn Shaddad; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Hafs bin Ghyath حفص بن غياث; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Maymuna bint al-Harith; Sulaiman bin Abi Sulaiman سليمان بن أبي سليمان (Sunan Abi Dawud)
I and the Messenger of Allah (ﷺ) used to lie in one cloth at night while I was menstruating. If anything from me smeared him, he washed the same place (that was smeared), and did not wash beyond it. If anything from him smeared his clothe, he washed the same place and did not wash beyond that, and prayed with it (i.e. the clothe).
Grade: Sahih

Hadith #2190 - Sunan Abi Dawud - Abdur Rahman ibn al-Harith; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; al-Walid bin Kathir al-Makhzumi الوليد بن كثير المخزومي; Hammad bin Usamah حماد بن أسامة - أبو أسامة (Sunan Abi Dawud)
The Prophet (ﷺ) said: There is no divorce except in what you possess; there is no possession, there is no sale transaction till you possess. The narrator Ibn as-Sabbah added: There is no fulfilling a vow till you possess.
Grade: Hasan Sahih

Hadith #2212 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Ibn Ishaq محمد بن إسحاق بن يسار‎; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث; Uthman bin Muhammad (Sunan Abi Dawud)
Abu Hurairah reported the Prophet(ﷺ) as saying Abraham(peace be upon him) never told a lie except on three occasions twice for the sake of Allaah. Allaah quoted his words (in the Qur’an) “I am indeed sick” and “Nay, this was done by – this is their biggest one”. Once he was passing through the land of a tyrant (king). He stayed there in a place. People went to the tyrant and informed him saying “A man has come down here; he has a most beautiful woman with him.” So he sent for h
Grade: Sahih

Hadith #2306 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; ibn Mas'ud; Masrouq bin al-Ajda' مسروق بن الأجدع; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Muslim bin Sabih al-Hamdani, Abu al-Daha مسلم بن صبيح أبو الضحى; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Uthman bin Muhammad (Sunan Abi Dawud)
‘Ubaid Allah bin ‘Abd Allah bin ‘Utbah said that his father wrote (a letter) to ‘Abd Allaah bin Al Arqam Al Zuhri asking him to visit Subai’ah daughter of Al Harith Al Aslamiyyah and ask her about her story and what the Apostle of Allaah(ﷺ) said to her when she asked his opinion (about her). So, ‘Umar bin Abd allah wrote in reply to ‘Abd Allah bin ‘Utbah informing him what she told him. She told that she was under (i.e., the wife of) Sa’d bin Khawlah who belonged to Banu Amir
Grade: Sahih

Hadith #2358 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Asma' bint Abi Bakr; Fatima bint al-Mundhir bin al-Zubayr فاطمة بنت المنذر بن الزبير; Hammad bin Usamah حماد بن أسامة - أبو أسامة; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Hisham bin 'Urwa هشام بن عروة (Sunan Abi Dawud)
The Prophet of Allah (ﷺ) used to say when he broke his fast: O Allah, for Thee I have fasted, and with Thy provision I have broken my fast.
Grade: Da'if

Hadith #2561 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; ibn Abbas; Mujahid bin Jabir مجاهد بن جبر; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan Abi Dawud)
‘Imran bin Hussain said “The Prophet (ﷺ) was on a journey. He heard a curse. He asked “What is this? They (the people) said “This is so and so (a woman) who cursed her riding beast. The Prophet (ﷺ) said “Remove the saddle from it, for it is accursed. So, they removed (the saddle) from it. ‘Imran said “As if I am looking at it a grey she Camel.”
Grade: Sahih

Hadith #2586 - Sunan Abi Dawud - Abu Barda bin Abi Musa al-Asha'ari أبو بردة / الحارث بن أبي موسى الأشعري; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Abu Musa al-Asha'ari; Bryd bin 'Abdullah بريد بن عبد الله بن أبي; Hammad bin Usamah حماد بن أسامة - أبو أسامة (Sunan Abi Dawud)
Jabir said “The Apostle of Allaah(ﷺ) ordered a man who was distributing arrows not to pass the mosque with them except that he is holding their heads.
Grade: Sahih

Hadith #2683 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Amr bin 'Uthman عمرو بن عثمان بن عفان; Uthman ibn 'Affaan; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan Abi Dawud)
On the day when Mecca was conquered, the Messenger of Allah (ﷺ) gave protection to the People except four men and two women and he named them. Ibn AbuSarh was one of them. He then narrated the tradition. He said: Ibn AbuSarh hid himself with Uthman ibn Affan. When the Messenger of Allah (ﷺ) called the people to take the oath of allegiance, he brought him and made him stand before the Messenger of Allah (ﷺ). He said: Messenger of Allah, receive the oath of allegiance from him. He raised his
Grade: Sahih

Hadith #2703 - Sunan Abi Dawud - Abdullah bin Abi Awfa; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Sulaiman bin Abi Sulaiman سليمان بن أبي سليمان (Sunan Abi Dawud)
AbuLabid said: We were with AbdurRahman ibn Samurah ibn Kabul. The people got booty and plundered it. He stood and addressed (the people): I heard the Messenger of Allah (ﷺ) prohibiting getting property from the booty before its distribution. Therefore, they returned what they had taken, He then distributed it among them.
Grade: Sahih

Hadith #2708 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Ibrahim bin Yusuf bin Ishaq إبراهيم بن يوسف بن إسحاق; Yusuf bin Ishaq bin Abi Ishaq يوسف بن إسحاق بن أبي إسحاق (Sunan Abi Dawud)
The Prophet (ﷺ) said: He who believes in Allah and the Last Day must not ride on packhorse belonging to the booty of the Muslims and put it back when he has emaciated it; and he who believes in Allah and the Last Day must not wear a garment belonging to the booty of the Muslims and put it back when he made it threadbare.
Grade: Hasan Sahih

Hadith #2724 - Sunan Abi Dawud - Abu Barda bin Abi Musa al-Asha'ari أبو بردة / الحارث بن أبي موسى الأشعري; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Abu Musa al-Asha'ari; Bryd bin 'Abdullah بريد بن عبد الله بن أبي; Hammad bin Usamah حماد بن أسامة - أبو أسامة (Sunan Abi Dawud)
Abu Hurairah said “I came to Madeenah when the Abu Apostle of Allaah(ﷺ) was in Khaibar, after it was captured. I asked him to give me a share from the booty. A son of Sa’id bin Al ‘As spoke and said “Do not give him any share, Apostle of Allaah(ﷺ). I said “This is the killer of Ibn Qauqal.” (The son of) Sa’id bin Al ‘As said “Oh, how wonderful! A Wabr who came down to us from the peak of Dal blames me of having killed a Muslim whom Allaah honored at my hands and did not dis
Grade: Sahih

Hadith #2765 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; al-Miswar bin Makhrama bin Nawfal; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ibn Ishaq محمد بن إسحاق بن يسار‎; Marwan bin al-Hakam bin Abi al-'As; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) came out in the year of al-Hudaibbiyyah with over ten hundreds of Companions and when he came to Dhu al Hulaifah. He garlanded and marked the sacrificial animals, and entered the sacred state of Umrah. He then went on with the tradition. The Prophet moved on and when he came to the mountain, pass by which one descends (to Mecca) to them, his riding-beast knelt down, and the people said twice: Go on, go on, al-Qaswa has become jaded. The Prophet (May peace be upon him
Grade: Sahih

Hadith #2862 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Aisha bint Abi Bakr; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Masrouq bin al-Ajda' مسروق بن الأجدع; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Shaqayq bin Salmah al-Asadi شقيق بن سلمة الأسدي أبو وائل الكوفي; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: It is the duty of a Muslim man who has something which is to be given as bequest not to have it for two nights without having his will written regarding it.
Grade: Sahih

Hadith #2883 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Hisham bin 'Urwa هشام بن عروة; Jabir ibn 'Abdullah; Shu'aib bin Ishaq bin 'Abdur Rahman شعيب بن إسحاق بن عبد الرحمن; Wahb bin Kysan al-Quraishi وهب بن كيسان القرشي (Sunan Abi Dawud)
On his father’s authority, said that his grandfather told that Al-‘As ibn Wa’il left his will that a hundred slaves should be emancipated on his behalf. His son Hisham emancipated fifty slaves and his son Amr intended to emancipate the remaining fifty on his behalf, but he said: I should ask first the Messenger of Allah (ﷺ). He, therefore, came to the Prophet (ﷺ) and said: Messenger of Allah, my father left in his will that a hundred slaves should be emancipated on his behalf and Hisha
Grade: Hasan

Hadith #3120 - Sunan Abi Dawud - Abdullah bin Mubarak عبد الله بن المبارك; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Ma'qil bin Yasar al-Mazni; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي (Sunan Abi Dawud)
The Prophet (ﷺ) was covered with striped Yemen garment (after his death).
Grade: Sahih

Hadith #3195 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Amir al-Sha'bi عامر الشعبي (Sunan Abi Dawud)
I prayed behing the Prophet (ﷺ) over a woman who died in childbirth, and he stood opposite her waist.
Grade: Sahih

Hadith #3250 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; al-Hasan bin 'Ubaidullah الحسن بن عبيد الله بن عروة; Sa'd bin 'Ubaida al-Salmi سعد بن عبيدة السلمي أبو حمزة (Sunan Abi Dawud)
” ‘Umar said: I swear by Allah, I never swore by it personally or reporting it from others.”
Grade: Sahih

Hadith #3285 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Mas'ar bin Kadam مسعر بن كدام; Smak bin Hrb bin Aws سماك بن حرب بن أوس (Sunan Abi Dawud)
The Prophet (ﷺ) said: I swear by Allah, I shall fight against the Quraysh; I swear by Allah, I shall fight against the Quraysh; I swear by Allah, I shall fight against the Quraysh. He then said: “If Allah wills.” Abu Dawud said: A number of persons have narrated this tradition from Sharik, from Simak, from ‘Ikrimah, from Ibn ‘Abbas who reported from the Prophet (ﷺ): “But he did not fight against them.”
Grade: Sahih

Hadith #3309 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Muslim bin 'Imran al-Batayn مسلم بن عمران البطين; Sa'id bin Jubayr سعيد بن جبير الأسدي; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
A woman came to the Prophet (ﷺ) and said: I gave a slave girl to my mother, but she died and left the salve-girl. He said: Your reward became certain for you, and she (the slave-girl) returned to you as inheritance. She said: She died and one month’s fast was due from her. He (the narrator) then mentioned the tradition similar to the one mentioned by ‘Amr b. ‘Awn.
Grade: Sahih

Hadith #3331 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Asim bin Kulayb bin Shahab عاصم بن كليب بن شهاب بن المجنون; Kulayb bin Shahab كليب بن شهاب (Sunan Abi Dawud)
The Prophet (ﷺ) said: A time is certainly coming to mankind when only the receiver of usury will remain, and if he does not receive it, some of its vapour will reach him. Ibn Isa said: Some of its dust will reach him.
Grade: Da'if

Hadith #3386 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Hammad bin Usamah حماد بن أسامة - أبو أسامة; ibn Umar; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Umar bin Hamza bin 'Abdullah عمر بن حمزة بن عبد الله بن عمر (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) sent with him a dinar to buy a sacrificial animal for him. He bought a sheep for a dinar, sold it for two and then returned and bought a sacrificial animal for a dinar for him and brought the (extra) dinar to the Prophet (ﷺ). The Prophet (ﷺ) gave it as alms (sadaqah) and invoked blessing on him in his trading.
Grade: Da'if

Hadith #3534 - Sunan Abi Dawud - Abu Hurairah; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Ahmed bin Ibrahim bin Kathir أحمد بن إبراهيم بن كثير; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Sharayk bin 'Abdullah شريك بن عبد الله النخعي; Talq bin Ghanam طلق بن غنام; Uthman bin 'Asim bin Husayn عثمان بن عاصم بن حصين أبو حصين (Sunan Abi Dawud)
I used to write (the account of) the expenditure incurred on orphans who were under the guardianship of so-and-so. They cheated him by one thousand dirhams and he paid these (this amount) to them. I then got double the property which they deserved. I said (to the man: Take one thousand (dirhams) which they have taken from you (by cheating). He said: No, my father has told me that he heard the Messenger of Allah (ﷺ) say: Pay the deposit to him who deposited it with you, and do not betray him wh
Grade: Sahih

Hadith #3576 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Rja'a al-Ansari رجاء الأنصاري; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
“If any do fail to judge (by the light of) what Allah has revealed, they are (no better than) unbelievers” up to “wrongdoers.” These three verses were revealed about the Jews, particularly about Quraizah and al-Nadir.
Grade: Hasan

Hadith #3637 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; al-Walid bin Kathir al-Makhzumi الوليد بن كثير المخزومي; Hammad bin Usamah حماد بن أسامة - أبو أسامة (Sunan Abi Dawud)
A man disputed with az-Zubayr about streamlets in the lava plain which was irrigated by them. The Ansari said: Release the water and let it run, but az-Zubayr refused. The Holy Prophet (ﷺ) said to az-Zubayr: Water (your ground), Zubayr, then let the water run to your neighbour. The Ansari then became angry and said: Messenger of Allah! it is because he is your cousin! Thereupon the face of the Messenger of Allah (ﷺ) changed colour and he said: Water (your ground), then keep back the water ti
Grade: Sahih

Hadith #3849 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Abu Sa'id al-Khudri; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
When the food cloth was removed, the Messenger of Allah (ﷺ) said: “praise be to Allah abundantly and sincerely, of such a nature as is productive of blessing, is not insufficient, Abandoned, or ignored, O our lord.”
Grade: Sahih

Hadith #3882 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Amr bin Murrah bin 'Abdullah عمرو بن مرة بن عبد الله بن طارق; ibn Mas'ud; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Yahya bin al-Jazar al-Arni يحيى بن الجزار (Sunan Abi Dawud)
I intended to prohibit suckling during pregnancy (ghailah), but I considered the Greeks and the Persians and saw that they practiced it, without any injury being caused to their children thereby. Malik said : Ghailah means that a man has intercourse with a women while she is suckling a child.
Grade: Sahih

Hadith #3975 - Sunan Abi Dawud - Abdullah bin Mubarak عبد الله بن المبارك; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Anas ibn Malik; Uthman bin Muhammad; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
The Prophet (ﷺ) used to read: “Not equal are those believers who sit (at home) and receive no hurt (ghayru ulid-darari) but the narrator Sa’id did not say the words “used to read”
Grade: Hasan Sahih

Hadith #3997 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Abu Sa'id al-Khudri; Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Uthman bin Muhammad (Sunan Abi Dawud)
A man whom the Prophet (ﷺ) made the following verse read informed me, or he was informed by a man whom a man made the following verse read through a man whom the Prophet (ﷺ) made the following verse read: “For, that day His chastisement will be such as none (else) can be inflicted (la yu’adhdhabu) Abu Dawud said: ‘Asim, al-A’mash, Talhah b. Musarrif, Abu Ja’far Yazid b. al-Qa’qa’, Shaibah b. Nassah, Nafi’ b. ‘Abd al-Rahman, ‘Abd Allah b. Kathir al-Dari, Abu ‘Amr b. al-
Grade: Hasan

Hadith #4069 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; al-Walid bin Kathir al-Makhzumi الوليد بن كثير المخزومي; Hammad bin Usamah حماد بن أسامة - أبو أسامة; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Rafi' bin Khadij bin Rafi' (Sunan Abi Dawud)
A man wearing two red garments passed the Prophet (ﷺ) and gave him a greeting, but he did not respond to his greeting.
Grade: Da'if

Hadith #4111 - Sunan Abi Dawud - Abdullah bin Mubarak عبد الله بن المبارك; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Umm Salamah; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
The verse: “And say to the believing women that they should lower gaze was partly abrogated by the verse: “Such elderly women as are past the prospect of marriage.”
Grade: Hasan

Hadith #4189 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Asim bin Kulayb bin Shahab عاصم بن كليب بن شهاب بن المجنون; Kulayb bin Shahab كليب بن شهاب; Mua'wiya bin Hisham al-Qsar معاوية بن هشام القصار; Sufyan bin 'Uqba al-Swa'iy سفيان بن عقبة السوائي الكوفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Wa'il bin Hujr al-Kundi al-Hadrami (Sunan Abi Dawud)
When I parted the hair of the Messenger of Allah (ﷺ) I made a parting from the crow of his head and let his forelock hang between his eyes.
Grade: Hasan

Hadith #4195 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Anas ibn Malik; Thabit bin Aslam Albanani ثابت بن أسلم البناني; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan Abi Dawud)
The Prophet (ﷺ) saw a boy with part of his head shaved and part left unshaven. He forbade them to do that, saying: Shave it all or leave it all.
Grade: Sahih

Hadith #4206 - Sunan Abi Dawud - Abdul Malik bin Sa'id عبد الملك بن سعيد; Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Iyad bin Laqayt al-Sadusi إياد بن لقيط (Sunan Abi Dawud)
I went with my father to the Prophet (ﷺ). He had locks hanging down as far as the lobes of the ears stained with henna, and he was wearing two green garments.
Grade: Sahih

Hadith #4281 - Sunan Abi Dawud - Abu Bakr bin 'Ayyash al-Asadi أبو بكر بن عياش بن سالم الأسدي; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Ahmed bin Ibrahim bin Kathir أحمد بن إبراهيم بن كثير; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubaidullah bin Musa bin Abi al-Mukhtar عبيد الله بن موسى بن أبي المختار باذام; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان; Za'ida bin Qadama al-Thaqifi زائدة بن قدامة الثقفي (Sunan Abi Dawud)
When he came back to his home. the Quraish came to him and said: Then what will happen ? He said: Then turmoil will prevail.
Grade: Sahih

Hadith #4338 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Abu Sa'id al-Khudri; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Isma'il bin Raja'a bin Rabi'a al-Zubaidi إسماعيل بن رجاء بن ربيعة الزبيدي; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Qays bin Muslim al-Jadli قيس بن مسلم الجدلي; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Tariq bin Shahab (Sunan Abi Dawud)
You people recite this verse “You who believe, care for yourselves; he who goes astray cannot harm you when you are rightly-guided,” and put it in its improper place. Khalid’s version has: We heard the Prophet (ﷺ) say: When the people see a wrongdoer and do not prevent him, Allah will soon punish them all. Amr ibn Hushaym’s version has: I heard the Messenger of Allah (ﷺ) say: If acts of disobedience are done among any people and do not change them though the are able to do so, Allah
Grade: Sahih

Hadith #4343 - Sunan Abi Dawud - Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Ady bin 'Ady bin 'Umayra عدي بن عدي بن عميرة; al-Mughira bin Ziyad al-Bjly المغيرة بن زياد البجلي أبو هشام (Sunan Abi Dawud)
When we were around the Messenger of Allah (ﷺ), he mentioned the period of commotion (fitnah) saying: When you see the people that their covenants have been impaired, (the fulfilling of) the guarantees becomes rare, and they become thus (interwining his fingers). I then got up and said: What should I do at that time, may Allah make me ransom for you? He replied: Keep to your house, control your tongue, accept what you approve, abandon what you disapprove, attend to your own affairs, and leave
Grade: Hasan Sahih

Hadith #4354 - Sunan Abi Dawud - Abdul Malik bin 'Umayr al-Qabti عبد الملك بن عمير بن سويد القبطي; Abu Da'ud أبو داود السجستاني الأزدي; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Hafs bin Ghyath حفص بن غياث; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان; Sulaiman bin Abi Sulaiman سليمان بن أبي سليمان (Sunan Abi Dawud)
I went to the Prophet (ﷺ) while two men who were Ash’ arIs were with me. One of them was on my right and the other on my left side. Bothe of them asked him for employment. The prophet (ﷺ) was silent. He asked : What do you say Abu Musa, or ‘Abd Allah b. Qais (Abu Musa’s name)? I replied: By him who has sent you with truth, they did not inform me of what they had in their hearts, and I did not know that they would ask for an employment. He said : I have the scene before my eyes that h
Grade: Sahih

Hadith #4446 - Sunan Abi Dawud - Abdullah bin Marrah al-Kharfi عبد الله بن مرة الهمداني الخارفي; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; al-Bara' bin Azib bin al-Harith; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
some jews came to the Messenger of Allah (ﷺ) and mentioned to him that a man and a women of their number had committed fornication. The Messenger of Allah (ﷺ) asked them: What do you find in the Torah about stoning? They replied: We disgrace them and they should be flogged. ‘Abd Allah b. Salam said: You lie; it contains (instruction for) stoning. So they brought the Torah and spread it out, and one of them put his hand over the verse of stoning and read what preceded it and what followed i
Grade: Sahih

Hadith #4492 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Ali bin Salah bin Salah علي بن صالح بن صالح بن حي; ibn Abbas; Ikrama عكرمة; Smak bin Hrb bin Aws سماك بن حرب بن أوس; Ubaidullah bin Musa bin Abi al-Mukhtar عبيد الله بن موسى بن أبي المختار باذام (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say. . . He then mentioned the tradition to the same effect.
Grade: Sahih

Hadith #4585 - Sunan Abi Dawud - Abdul 'Aziz bin 'Umar bin 'Abdul-'Aziz عبد العزيز بن عمر بن عبد العزيز; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Hafs bin Ghyath حفص بن غياث (Sunan Abi Dawud)
The Prophet (ﷺ) said to the man bit him: If you wish that you give him control over your hand and he bites it, and then you drive it away from his mouth (you may do it). He imposed no retaliation for his teeth.
Grade: Sahih

Hadith #4641 - Sunan Abi Dawud - Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Asim al-Ahwal عاصم الأحول; Hajjaj bin Muhammad al-Musaysi حجاج بن محمد المصيصي الأعور (Sunan Abi Dawud)
I heard al-Hajjaj addressing the people say: The similitude of ‘Uthman with Allah is like the similitude of Jesus son of Mary. He then recited the following verse and explained it: “Behold! Allah said: O Jesus! I will take thee and raise thee to Myself and clear thee (of the falsehood) of those who blaspheme.” He was making a sign with his hand to us and to the people of Syria.
Grade: Hasan

Hadith #4646 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abdullah bin Zalm عبد الله بن ظالم التميمي المازني; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Hilal bin Yasaf هلال بن يساف; Husayn bin 'Abdur Rahman al-Salmi حصين بن عبد الرحمن السلمي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Sa'id bin Zayd; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) said: The Caliphate of Prophecy will last thirty years; then Allah will give the Kingdom of His Kingdom to anyone He wills. Sa’id told that Safinah said to him: Calculate Abu Bakr’s caliphate as two years, ‘Umar’s as ten, ‘Uthman’s as twelve and ‘Ali so and so. Sa’id said: I said to Safinah: They conceive that ‘Ali was not a caliph. He replied: The buttocks of Marwan told a lie.
Grade: Hasan Sahih

Hadith #4730 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Hammad bin Usamah حماد بن أسامة - أبو أسامة; ibn Umar; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Umar bin Hamza bin 'Abdullah عمر بن حمزة بن عبد الله بن عمر; Uthman bin Muhammad (Sunan Abi Dawud)
The people asked : Messenger of Allah! Shall we see our lord, the Exalted, on the Day of resurrection? He replied : Do you feel any trouble in seeing the sun at noon when it is not in the cloud? They said: No. He asked : Do you feel any trouble in seeing the moon on the night when it is full and not in the cloud? They replied: No. He said: By him in whose hand my soul is, you will not feel any trouble in seeing him except as much as you feel in seeing any of them.
Grade: Sahih

Hadith #4836 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Jabir ibn 'Abdullah; Mas'ar bin Kadam مسعر بن كدام; Muhammad bin Bashr bin al-Farafsa محمد بن بشر بن الفرافصة العبدي (Sunan Abi Dawud)
I came to the Prophet (ﷺ). The people began to praise me and make a mention of me. The Messenger of Allah (ﷺ) said: I know you, that is, he knew him. I said: My father and mother be sacrificed for you! you were my partner and how good a partner ; you neither disputed nor quarrelled.
Grade: Sahih

Hadith #4868 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Abu Sa'id al-Khudri; Hammad bin Usamah حماد بن أسامة - أبو أسامة; Ibrahim bin Musa al-Razi al-Fara' إبراهيم بن موسى الرازي الفراء; Umar ibn al-Khattab (Sunan Abi Dawud)
The Prophet (ﷺ) said: When a man tells something and then departs, it is a trust.
Grade: Sahih

Hadith #4898 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Ata' bin Abi Rabah عطاء بن أبي رباح; ibn Umar; Imran bin Anas عمران بن أنس; Mua'wiya bin Hisham al-Qsar معاوية بن هشام القصار (Sunan Abi Dawud)
Ibn Awn said: I asked about the meaning of intisar (revenge) in the Qur’anic verse: “But indeed if any do help and defend themselves (intasara) after a wrong (done) to them, against them there is no cause of blame.” Then Ali ibn Zayd ibn Jad’an told me on the authority of Umm Muhammad, the wife of his father. Ibn Awn said: It was believed that she used to go to the Mother of the Faithful (i.e. Aisha). She said: The Mother of the Faithful said: The Messenger of Allah (ﷺ) came upon me wh
Grade: Da'if

Hadith #4917 - Sunan Abi Dawud - Abu al-Darda; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Amr bin Murrah bin 'Abdullah عمرو بن مرة بن عبد الله بن طارق; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Umm al-Darda'a أم الدرداء (Sunan Abi Dawud)
Avoid suspicion for suspicion is the most lying form of talk. Do not be inquisitive about one another, or spy on one another.
Grade: Sahih

Hadith #4926 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Hashim al-Rmany أبو هاشم الرماني; Abu Hurairah; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; al-Mfdl bin Yonus al-J'fy Abu المفضل بن يونس الجعفي; Hammad bin Usamah حماد بن أسامة - أبو أسامة; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال (Sunan Abi Dawud)
When we were with Ibn ‘Umar, he heard the sound of a man who was blowing a pipe. He then mentioned a similar tradition. Abu Dawud said : This is more rejected.
Grade: Sahih

Hadith #5091 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Qatada قتادة; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan Abi Dawud)
if anyone says a hundred times in the morning: “Glory be to Allah, the Sublime, and I begin with praise of him”, and says likewise in the evening, no one from the creatures will bring anything like the one which he will bring.
Grade: Sahih

Hadith #5140 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abdur Rahman bin Sulaiman ibn al-Ghasil عبد الرحمن بن سليمان - ابن الغسيل; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Uthman bin Muhammad (Sunan Abi Dawud)
Messenger of Allah! to whom should I show kindness? He said: Your mother, your sister, your brother and the slave whom you set free and who is your relative, a due binding (on you), and a tie of relationship which should be joined.
Grade: Da'if

Hadith #5157 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Abu Mas'ud al-Badri; Ibrahim bin Yazid - Taym al-Rabab إبراهيم بن يزيد بن شريك تيم الرباب; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Yazid bin Sharayk bin Tariq يزيد بن شريك بن طارق التيمي الكوفي (Sunan Abi Dawud)
I saw Abu Dharr at Rabadhah. He was wearing a thick cloak, and his slave also wore a similar one. He said : the people said: Abu Dharr! (it would be better) if you could take the cloak which your slave wore, and you combined that with, and it would be a pair of garments (hullah) and you would clothe him with another garment. He said: Abu Dharr said : I abused a man whose mother was a non-Arab and I reviled him for his mother. He complained against me to the apostle of allah (May peace be upon hi
Grade: Sahih